2019
DOI: 10.1016/j.neuropharm.2019.02.024
|View full text |Cite
|
Sign up to set email alerts
|

HIV gp120 upregulates tonic inhibition through α5-containing GABAARs

Abstract: HIV-Associated Neurocognitive disorder (HAND) affects nearly half of infected patients. The HIV envelope protein gp120 is shed by infected cells and is a potent neurotoxin in vitro that reproduces many aspects of HAND when expressed in vivo. Here, we show that HIV gp120 increases the amplitude of a tonic current mediated by γ-aminobutyric acid type-A receptors (GABA A Rs). Treating rat hippocampal cultures with 600 pM gp120 IIIB for 4 h increased a tonic bicucullinesensitive current, which remained elevated fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 58 publications
(80 reference statements)
1
5
0
Order By: Relevance
“…The mainly neuronal location of CXCR3 confirms and explains why intrathecally administered CXCR3 ligands induce fast and strong pain-like behaviors in naive mice [28]. The binding of ligands to CXCR3 is associated with an increase in the intracellular Ca 2+ concentration and the activation of MAPKs and NF-κB, which, as is well known, contributes to the development of hypersensitivity [296][297][298][299]. Therefore, the single and repeated intrathecal administration of a potent and selective CXCR3 antagonist ((±)-NBI-74330) attenuates neuropathic pain symptoms.…”
Section: Cxcr3supporting
confidence: 55%
“…The mainly neuronal location of CXCR3 confirms and explains why intrathecally administered CXCR3 ligands induce fast and strong pain-like behaviors in naive mice [28]. The binding of ligands to CXCR3 is associated with an increase in the intracellular Ca 2+ concentration and the activation of MAPKs and NF-κB, which, as is well known, contributes to the development of hypersensitivity [296][297][298][299]. Therefore, the single and repeated intrathecal administration of a potent and selective CXCR3 antagonist ((±)-NBI-74330) attenuates neuropathic pain symptoms.…”
Section: Cxcr3supporting
confidence: 55%
“…For example, we have recently shown that exposure to gp120 IIIB leads to dendritic spine deficits in cultured cortical neurons in a process that requires secretion of interleukin-1β (IL-1β) from co-cultured glial cells, suggesting that IL-1β is an important contributor to HIV-induced spine deficits in the cortex [ 90 ]. Other studies in rat hippocampal cultures have shown that gp120 IIIB increased inhibitory synapses and tonic inhibition, which also required gp120-induced secretion of IL-1β from microglia in the same cultures [ 114 , 115 ]. Since IL-1β indirectly activated NMDA receptors in these neurons [ 114 ], the shift toward inhibitory input may represent an adaptive mechanism that could at least partially explain why hippocampal neurons are not as hyper-excitable as other types of neurons in animal models of HAND.…”
Section: Synapodendritic Damage and Neuronal Activity Changes In Hand Experimental Modelsmentioning
confidence: 99%
“…Two recent studies have identified mechanistic insights on how this occurs in gp120-treated hippocampal neurons. In the first, a 4-h treatment with gp120 IIIB increased inhibitory currents by enhancing the surface expression of neuronal α5 subunit-containing GABA A receptors, and these outcomes were mediated by gp120-induced secretion of IL-1β from microglia and activation of neuronal p38 mitogen-activated protein kinase [ 115 ]. In the second study, a 24-h treatment with gp120 IIIB increased the number of gephyrin-labeled inhibitory synapses, which also involved IL-1β activation of p38 in addition to NMDA receptor and Src kinase-mediated protein synthesis [ 114 ].…”
Section: Mechanisms That Affect Synaptodendritic Damage and Network Dysfunction In Handmentioning
confidence: 99%
“…HIV-1 has a lipid envelope and its surface-attached glycoprotein gp120 can bind to the CD4 receptor on host cells, which is a key step in HIV infection of host cells ( Figure 4 A) [ 61 , 62 , 63 ]. That is, gp120 glycoprotein is a potential target for the binding of Ag NPs.…”
Section: Antiviral Performances Of Different Metallic Materialsmentioning
confidence: 99%